The Spread of Organized Retailing in India-With a Special Reference to Vijayawada City - Prasad, V. Vijay Durga (Indian Journal of Marketing, 2007)
The retail institutions play a crucial role in attracting and satisfying target customers. The diversity and changing nature of society has compelled retailers to change their store formats to provide a complete shopping experience to customers. With the population of over one billion and a middle class population of over three hundred millions organized retailing is still in its infancy in the country. This is largely due to the prevailing retailing system that was established with the kirana stores that continue to meet all the requirements of the purchasers albeit without the convenience of the shopping as provided by the retail chains. However the transformation is underway and India has joined the organized retail revolution that was rapidly transforming the economies. Organised retailing is spreading and making its presence felt in different parts of the country. The retailing industry has entered a new phase, new retail formats built around different pricing and service strategies have evolved. Department stores and cooperatives are giving way to new formats like hypermarkets, convenience stores etc., In this backdrop a study was carried out on the spread of organized retailing in India with a special reference to Vijayawada city of Andhra Pradesh.